The Influence of Company Size, Audit Quality, Profitability, and Audit Committee on the Timeliness of Financial Report Submission (Study on Coal Mining Companies Listed on the Idx for the 2021-2023 Period) - Kaylee Milano; Riadi; Jeannette Patricia; Debi Masri (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This study aims to analyze the influence of Company Size, Audit Quality, Profitability, and Audit Committee on the timeliness of financial report submission. The research method uses a quantitative approach. The population used in this research are companies listed on the coal mining index on the Indonesia Stock Exchange in the 2021-2023 period. The research samples obtained were 23 coal mining sub-sector companies with 69 observations. The results of the research show that company size does not partially influence the timeliness of financial report submission. Audit quality partially has a negative and significant influence on the timeliness of financial report submission. Profitability partially has a positive and significant influence on the timeliness of submitting financial reports. The Audit Committee partially has no influence on the timeliness of financial report submission.